Fragmented Approach to Spatial Management in Indonesia: When it Will Be Ended? - Widiatedja, I Gusti Ngurah Parikesit (Kertha Patrika, 2021)
As a regulatory tool, spatial planning is important as it directs socio-economic development and prevents environmental and social damage by commercial and public projects. There should be an integrated spatial management to ensure the effective use of restricted spatial resources, balancing infrastructural, industrial and commercial business development with the available resources, including land, forest, and marine. However, the fragmented approach to spatial management has been thrived since the independence of Indonesia. The newly controversial Law No. 11 of 2020 on Job Creation has emerged a big hope that Indonesia will end the fragmented approach to spatial management. However, this Law seems to maintain this approach by enacting four different governmental regulation for four spatial issues, namely land use planning; forestry; energy and mineral resources; and marine and fishery. This fragmented approach has adverse consequences as it leads to overlapping authorities that may end up with disharmony and conflicting regulations. Besides, the insistence to employ fragmented approach to spatial management has linked to oligarchy issue as shown by old older, new order and the regional autonomy era.